Linkage disequilibrium between FD1-D9S202 haplotypes and the Friedreich's ataxia locus in a central-southern Italian population. Issue 2 (February 1994) - Pianese, L; Cocozza, S; Campanella, G; Castaldo, I; Cavalcanti, F; De Michele, G; Filla, A; Monticelli, A; Munaro, M; Redolfi, E
Abstract : We used two recently described genetic markers in the region of the Friedreich's ataxia locus to study 33 affected pedigrees from central-southern regions of Italy. These markers are predicted, by physical mapping, to be localised more closely to the Friedreich's ataxia locus than other previously described markers. No recombination was found between these markers and the disease locus. Strong linkage disequilibrium is present between the compound haplotype and the disease locus. Since this population was also previously studied by using three other more distal genetic markers, a total of five markers has been used to identify the extended haplotype. Homozygosity in consanguineous pedigrees was also studied. Extended haplotype analysis and homozygosity studies suggest the presence of few common disease causing mutations in our population.